2013
DOI: 10.2175/106143012x13415215906690
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analyses of Inputs of Municipal Wastewater Effluent and Coupled Impacts on an Urban Lake

Abstract: A retrospective review and analysis are presented of the evolution of treatment, point of discharge considerations, and constituent loading from the Metropolitan Syracuse Wastewater Treatment Plant (Metro), and the coupled water quality effects on the receiving urban lake (Onondaga Lake, New York) from the early 1970s to 2010. The analysis is based on long-term monitoring of the discharge, Onondaga Lake, and a nearby river system considered as a potential alternate to receive the effluent. The Metro discharge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Effler et al (2013) showed that with a reduction of pollutant input, the water quality of a lake can improve dramatically in a relatively short period. In addition, an immediate shortterm, but partial solution, may be artificial aeration.…”
Section: > Impact Of Wastewater Discharges and Possible Solutionsmentioning
confidence: 99%
“…Effler et al (2013) showed that with a reduction of pollutant input, the water quality of a lake can improve dramatically in a relatively short period. In addition, an immediate shortterm, but partial solution, may be artificial aeration.…”
Section: > Impact Of Wastewater Discharges and Possible Solutionsmentioning
confidence: 99%
“…Through the 1990s the Metro discharge caused severe water quality problems in the lake, primarily associated with high concentrations of ammonia and nitrite nitrogen, which violated standards to protect against their toxic effects, and severe cultural eutrophication (hypereutrophy) and its negative water quality manifestations (Effler et al ., ). These conditions have greatly improved from implementation of advanced treatment technologies at Metro.…”
Section: Methodsmentioning
confidence: 97%
“…These conditions have greatly improved from implementation of advanced treatment technologies at Metro. Year‐round nitrification treatment (2004) eliminated in‐lake violations of the nitrogen toxicity standards (Effler et al ., ). The resulting higher lake nitrate (NO 3 − ) concentrations were not deemed problematic with respect to phytoplankton growth, as reductions in phosphorus (P) were instead targeted to limit growth.…”
Section: Methodsmentioning
confidence: 99%
“…Contemporary municipal waste inputs include: (1) direct discharge (~3 m 3 /s) of effluent from a wastewater treatment plant (WWTP), (2) discharge from combined sewer overflows (CSOs) to tributaries during runoff events (Figure ), and (3) inputs from leaky sewers via these tributaries. Major reductions in phosphorus (P) loading from the WWTP have transformed the lake from hypereutrophy to mesotrophy (Effler et al ., , ), and brought increased focus to tributary inputs to achieve additional water quality improvements. As a result, the transport and fate of the tributary inflows within this lake have potentially important implications.…”
Section: Study Systemmentioning
confidence: 97%